PROSES PEMBUATAN TABUNG GAS 12 KG MENGGUNAKAN MATERIAL JIS-SG 255 - Christofel Jarot Yudaputranto; Supriyono Supriyono (Jurnal Ilmiah Teknik, 2024)
A gas cylinder is a container in the shape of a tube and is used to store gas produced from oil refineries. The manufacturing process goes through various processes and the selection of strong materials to withstand the gas pressure in the cylinder. The main materials used in making the 12 kg gas cylinder are JIS SG 255 and SPHC. The 12 kg tube was designed with a tube height of 750 mm and a diameter of 280 mm. The SMAW welding process was carried out for the circumference and GMAW welding for the handguard and footring. To determine the area and volume of the weld on the 12 kg gas cylinder, area and volume calculations were carried out, so that it can be seen that the surface area of the 12 kg gas cylinder is 30.772 mm2, while the weld volume of the tube is known to be 115.395 cm3. Then, after welding the gas cylinder, proceed with annealing to restore the condition of the tube after welding with gradual heat temperatures, namely 200°C, 600°C and 200°C with a time of ± 14 minutes. Leak testing on tubes is carried out with two types of tests, namely hydrostatic tests and leak tests, hydrostatic tests on tubes use 31 bar water pressure with a quality of 50%, while for this leak test the tube is given air to find out whether the gas cylinder has a leak or not with a quality of 100 %.